2017
DOI: 10.1038/s41598-017-08203-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid glycosides isolated from Epimedium brevicornum and their estrogen biosynthesis-promoting effects

Abstract: Epimedium brevicornum Maxim has a long history of use in the treatment of estrogen deficiency-related diseases. However, the chemical constituents and mechanism of action of this medicinal plant are not fully understood. In the present study, we isolated four new isoprenylated flavonoid glycosides, as well as 16 known flavonoids (13 isoprenylated flavonoids), from this plant. The chemical structures of the new flavonoid glycosides were elucidated by extensive spectroscopic analysis. The new compounds 1–4 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Our results showed that supplementation with 50-100 mg/kg ICA increased AC, cAMP, and PKA mRNA levels in ovarian tissues, and that at the translational level, ICA activated the AC/cAMP/PKA/CREB pathway by increasing intracellular cAMP and PKA expression and CREB phosphorylation. These findings were consistent with those of several previous studies, which showed that ICA treatment could activate AC/cAMP/PKA/CREB signaling by increasing intracellular cAMP levels and facilitating phosphorylation of both PKA and CREB in rat calvarial osteoblasts (Shi et al, 2017) and human ovarian granulosa-like KGN cells (Zaccolo and Movsesian, 2007;Li et al, 2017). Together, these results suggest that ICA may promote E 2 synthesis by promoting aromatase expression through cAMP/PKA/CREB signaling in ovaries of E. sinensis in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that supplementation with 50-100 mg/kg ICA increased AC, cAMP, and PKA mRNA levels in ovarian tissues, and that at the translational level, ICA activated the AC/cAMP/PKA/CREB pathway by increasing intracellular cAMP and PKA expression and CREB phosphorylation. These findings were consistent with those of several previous studies, which showed that ICA treatment could activate AC/cAMP/PKA/CREB signaling by increasing intracellular cAMP levels and facilitating phosphorylation of both PKA and CREB in rat calvarial osteoblasts (Shi et al, 2017) and human ovarian granulosa-like KGN cells (Zaccolo and Movsesian, 2007;Li et al, 2017). Together, these results suggest that ICA may promote E 2 synthesis by promoting aromatase expression through cAMP/PKA/CREB signaling in ovaries of E. sinensis in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…9 Furthermore, the isoprenylated flavonoids glycosides from E. brevicornum may induce beneficial health effects by promotion of estrogen biosynthesis. 10 Follicle stimulating hormone is a glycoprotein polypeptide hormone. Follicle stimulating hormone is one of the hormones essential in development and the function of female's ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, modern pharmacological studies exhibited that the Epimedium herb possessed wide pharmacological activities, such as anti‐sexual dysfunction, anti‐osteoporosis, anti‐tumour actions and modulating immunological function . In the last decades, hundreds of compounds have been isolated from “Yinyanghuo”, of which, prenylflavonol glycosides were considered as the major bioactive constituents, and were reported to possess important bioactivities, thus could be used as chemotaxonomic markers …”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] In the last decades, hundreds of compounds have been isolated from "Yinyanghuo", of which, prenylflavonol glycosides were considered as the major bioactive constituents, and were reported to possess important bioactivities, thus could be used as chemotaxonomic markers. 30,31 Generally, pure water exhibited low efficiency in extraction of prenylflavonol glycosides from E. pubescens Maxim, thus organic solutions such as methanol and ethanol were normally used in combination with various methods to achieve high extractability. [32][33][34] Among the reported methods, some exhibited high extraction efficiencies for prenylflavonol glucosides.…”
Section: Introductionmentioning
confidence: 99%